Building Differentiation of Piyungan Muhammadiyah High School through Radio Extracurricular School - Erwan Sudiwijaya; Budi Dwi Arifianto (Kontribusia : Research Dissemination for Community Development, 2023)
Piyungan Muhammadiyah High School is the only private high school in Piyungan District. To get students into PPDB, this school has to compete with two high schools, namely Piyungan 1 Public High School and Banguntapan State High School, as well as four vocational high schools, namely Budhi Dharma Piyungan Vocational School, Maarif Vocational School 1 Piyungan, Maarif 2 Piyungan Vocational School and Piyungan Muhammadiyah Vocational School. Compared to its competitors, SMA Muhammadiyah Piyungan still needs to have a positioning differentiator because the SBM development plan relied on a positioning that cannot be realized for PPDB 2022. For this reason, we formed a school radio extracurricular through workshops on writing scripts for air magazines and grants for mini radio station infrastructure. The implementation method we use is Observation, Pre-test & Post-test, Workshop and Radio station installation. Our findings are an increase in students' understanding of UGC, an increase in experience in writing air magazine scripts, an increase in awareness of the potential for schools to become UGC and an increase in students' abilities in making air magazines. School radio can be applied as positioning for SMA Muhammadiyah Piyungan.